Rape in Chicago : race, myth, and the courts - Flood, Dawn Rae (Women in American history., 2012)
Spanning a period of four tumultuous decades from the mid-1930s through the mid-1970s, this study reassesses the ways in which Chicagoans negotiated the extraordinary challenges of rape, as either victims or accused perpetrators.